1982
DOI: 10.1016/0047-6374(82)90113-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the synthesis of exportable and nonexportable proteins in parotid glands during aging

Abstract: The age-related differences in the synthesis of exportable and nonexportable proteins of the parotid salivary gland were compared in 2- and 24-months-old rats. Parotid slices from these rats were incubated in the presence of [14C]leucine and the amount of radioactivity incorporated into the water-soluble proteins of the postmicrosomal supernatant was compared. The exportable and nonexportable proteins were identified by electrophoretic separation of these proteins by comparing the banding patterns of the gel p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 46 publications
1
5
1
Order By: Relevance
“…Rates of total protein and amylase synthesis in unstimulated glands of older rats were less than in those of their younger counterparts, as shown previously (Kim, 1981;Kim et al, 1980Kim et al, , 1982 Hours After Stimulation Fig. 3.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Rates of total protein and amylase synthesis in unstimulated glands of older rats were less than in those of their younger counterparts, as shown previously (Kim, 1981;Kim et al, 1980Kim et al, , 1982 Hours After Stimulation Fig. 3.…”
Section: Discussionsupporting
confidence: 77%
“…such as the liver, muscle, brain, heart, testis and kidney [see Richardson (1981) for review]. We have shown that rates of synthesis of secretory proteins, especially a-amylase, decline with age in rat parotid salivary glands (Kim et al, 1980(Kim et al, , 1982Kim, 1981;Kim and Arisumi, 1985). This decline does not appear to be related to structural alterations in the cells (Kim, 1984).…”
Section: Introductionmentioning
confidence: 95%
“…It has been reported that reductions occur in the amylase content in saliva (Meyer et al, 1937;Meyer and Necheles, 1940;Chilla et al, 1974), as well as the secretion and the rate of flow of saliva (Bertram, 1967). We have shown previously that the rate of protein synthesis declines with age in rat parotid glands 1980, Kim, 19811, and that this decline reflects the reduction in the synthesis of secretory proteins (Kim et al, 1982;Kim and Calkins, 1983). These age-related changes that affect the salivary content and the synthesis of protein suggest that alterations occur in the structural elements of the secretory acinar cells of the gland.…”
mentioning
confidence: 89%
“…Considering age and gender, similar to other body organs, it has been clearly established that synthesis and secretion of enzymes in unstimulated saliva decrease with age (14,15) . This has been supported by a study conducted by Kalipatnapu et al who showed that increase in salivary protein and amylase in both males and females up through middle age and then the concentration of these constituents remain unaffected through the rest of adult life (15) .…”
Section: Introductionmentioning
confidence: 93%